Heartbreak Island - Kaaberbøl, Lene. (New York : Volo/Hyperion Books for Children, 2005)
Five magical friends, known as the Guardians, learn the power of forgiveness when they travel to a mysterious island in search of Taranee's brother who has become the victim of dark magic.
"A Taranee story"--Cover.
3.9
3-6.
Keywords: Witches -- Juvenile fiction; Brothers and sisters -- Juvenile fiction; Missing persons -- Juvenile fiction; Magic -- Juvenile fiction; Witches -- Fiction; Brothers and sisters -- Fiction; Missing persons -- Fiction; Magic -- Fiction; Witches -- Fiction; Siblings -- Fiction; Missing persons -- Fiction; Magic -- Fiction; Occult fiction; Occult fiction